2014
DOI: 10.9790/2402-08215357
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microbiological Parameters of Water and Waste Waters In and Around Vijayawada

Abstract: The microbiological parameters of water and waste waters in and around

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 1 publication
2
26
0
Order By: Relevance
“…Therefore, irrigation water with high EC reduces yield potential. Other studies also showed EC values to be in the ranges of 225 to 3350 μS/cm (Jayalakshmi et al, 2011(Jayalakshmi et al, ), 2130 μS/cm (Inoti et al, 2012) which are similar with our findings of Elala River.…”
Section: Electrical Conductivity (Ec)supporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, irrigation water with high EC reduces yield potential. Other studies also showed EC values to be in the ranges of 225 to 3350 μS/cm (Jayalakshmi et al, 2011(Jayalakshmi et al, ), 2130 μS/cm (Inoti et al, 2012) which are similar with our findings of Elala River.…”
Section: Electrical Conductivity (Ec)supporting
confidence: 83%
“…The findings also indicate that at 95% confidence level, there are no significant differences between the sites and are within the permissible limits set by WHO (2008) and FAO (Ayers and Westcot, 1994). Others also reported similar values of DO for river water bodies (Karikari et al, 2007;Jayalakshmi et al, 2011;Addo et al, 2013).…”
Section: Dissolved Oxygen (Do)mentioning
confidence: 51%
“…This phenomenon has also been reported by Golterman and Kouwe [55] [36] reported similar observations in Oyun and Opa Lakes respectively. The high content of chloride in the aquatic systems is responsible for a large amount of organic matter which in turn causes eutrophication [56]. Chloride was found optimum during the study ranged from 1.53 to 51.60 mgl -1 with a mean value of 10.11 ± 8.96 mgl -1 [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is important for its effects on the chemistry and biochemical reactions in the organisms; it also affects the efficiency of treatment units (Jayalakshmi et al, 2011), for example, in cold temperature, the viscosity increases. This in turn, diminishes the efficiency of settling of the solids present in water because of the resistance offered by high viscosity to downward motion of the particles as they settle.…”
Section: Temperaturementioning
confidence: 99%